2018
DOI: 10.12659/pjr.900643
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Coronary Artery Calcium Score for Determination of Presence and Severity of Coronary Artery Disease

Abstract: SummaryBackgroundThere are controversies regarding the usefulness of coronary artery calcium score (CACS) for predicting coronary artery stenosis. The aim of this study was to determine the prognostic value of CACS for determining the presence and severity of coronary artery disease (CAD) in patients with sign and symptoms of the disease.Material/MethodsIn this cross-sectional study, 748 consecutive patients with suspected CAD, referred for coronary computed tomography angiography (CCTA), were enrolled. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In our study, the mean calcium score among participants was 382.45 ± 47.5 and the patients were classified as normal, minimal, mild, moderate and severe calcium scores. We found that the mean calcium score was significantly higher in patients with severe CAD (P<0.001).This was in agreement with Moradi M et al [15]. Also Almasi et al evaluated the value of CACS for predicting the presence and severity of CAD among 202 patients.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the mean calcium score among participants was 382.45 ± 47.5 and the patients were classified as normal, minimal, mild, moderate and severe calcium scores. We found that the mean calcium score was significantly higher in patients with severe CAD (P<0.001).This was in agreement with Moradi M et al [15]. Also Almasi et al evaluated the value of CACS for predicting the presence and severity of CAD among 202 patients.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the average CACS in different CAD groups were compared and found to be in agreement with the findings of another study in a similar population. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Te risk probability of developing coronary stenosis ≥50% remained consistent as the CACS increased beyond 230.8. Previous studies have indicated a positive correlation between higher CACS and an increased likelihood of coronary stenosis [24][25][26]. Tis study further suggested that a CACS of 63.6-66 is an infection point for coronary stenosis ≥50%.…”
Section: Discussionmentioning
confidence: 87%